Identification of Koumine as a Translocator Protein 18 kDa Positive Allosteric Modulator for the Treatment of Inflammatory and Neuropathic Pain - Xiong, Bojun; Jin, Guilin; Xu, Ying; You, Wenbing; Luo, Yufei; Fang, Menghan; Chen, Bing; Huang, Huihui; Yang, Jian; Lin, Xu; Yu, Changxi (Frontiers in Pharmacology, 2021)
Koumine is an alkaloid that displays notable activity against inflammatory and neuropathic pain, but its therapeutic target and molecular mechanism still need further study. Translocator protein 18 kDa (TSPO) is a vital therapeutic target for pain treatment, and recent research implies that there may be allostery in TSPO. Our previous competitive binding assay hint that koumine may function as a TSPO positive allosteric modulator (PAM). Here, for the first time, we report the pharmacological characterization of koumine as a TSPO PAM. The results imply that koumine might be a high-affinity ligand of TSPO and that it likely acts as a PAM since it could delay the dissociation of 3H-PK11195 from TSPO. Importantly, the allostery was retained in vivo, as koumine augmented Ro5-4864-mediated analgesic and anti-inflammatory effects in several acute and chronic inflammatory and neuropathic pain models. Moreover, the positive allosteric modulatory effect of koumine on TSPO was further demonstrated in cell proliferation assays in T98G human glioblastoma cells. In summary, we have identified and characterized koumine as a TSPO PAM for the treatment of inflammatory and neuropathic pain. Our data lay a solid foundation for the use of the clinical candidate koumine to treat inflammatory and neuropathic pain, further demonstrate the allostery in TSPO, and provide the first proof of principle that TSPO PAM may be a novel avenue for the discovery of analgesics.